GARMENT SECTOR OF BANGLADESH: VULNERABILITIES OF FEMALE WORKERS (Proceedings of the International Conference on Social Sciences, 2024)
The Readymade Garment (RMG) industry, contributing to 83% of Bangladesh's total export earnings, is a critical economic pillar. The sector offers employment opportunities for women who come from low-income backgrounds, making up about 80% of its workforce. Though the RMG industry brings noticeable socioeconomic changes for these women, their plight underscores the high cost of these gains. Female workers in this industry face numerous challenges, such as inadequate wages, unsafe working conditions, and gender-based discrimination, that adversely impact their physical and mental health. Using a qualitative research approach, this paper explores these vulnerabilities. The author visited three garment factories in Ashulia, Dhaka, observed the factories' working environments, and conducted group discussions and one-on-one interactions with 17 female workers. Moreover, a comprehensive review of secondary sources, such as recent literature, blog articles, and news reports, supplemented primary data collection. The author employed a thematic analysis of the gathered data and literature review, which reveals an industry marked by persistent job insecurities, inadequate transportation facilities, health hazards, and societal stigmas that predominantly affect female workers. The findings underline widespread workplace vulnerabilities, including physical and verbal abuse, hazardous working conditions, and gender-specific discrimination, with pregnancy-related discrimination being particularly noteworthy. The paper concludes with recommendations to mitigate these issues, emphasizing the shared responsibility of various stakeholders, including the Bangladesh government, the RMG sector, the International Labour Organization (ILO), and global clothing and fashion brands. The proposed recommendations comprise updating work standards, improving worker privileges such as increasing wages and transport facilities, ensuring building safety, and offering skill development opportunities. Implementing these measures can improve workers' facilities, augment productivity, and ensure sustainability in the success of Bangladesh's garment sector.
Keywords: Bangladesh RMG sector; garment industry; female workers; workplace vulnerabilities; gender-based discrimination; thematic analysis